SEISMIC PROTECTION OF EXISTING RC BUILDINGS USING FUSE ELEMENTS - (:unkn) unknown (WORLD SCIENTIFIC PUBL CO PTE LTD, 2012)
This paper presents a new concept on collapse prevention of existing RC buildings during a seismic event. The idea is to install steel panels in specified locations in the structure to reduce inter-story drifts. The panels are expected to work as a fuse in an electric circuit when a major earthquake occurs; the panels will attract the seismic forces and they may totally damaged but they will prevent severe damage in the main structural system. The proposed panels are light-weight, easy to handle, and can be constructed very quickly. Moreover, they are cheap and do not need formwork or skilled workers. To test the concept, a half-scale, single-story 3D reinforced concrete frame specimen was constructed at the shake-table laboratories of the Kandilli Observatory and Earthquake Research Institute of Bogazici University, and subjected to recorded real earthquake base accelerations. The amplitudes of base accelerations were increased until a moderate damage level is reached. Then, the damaged RC frames was retrofitted by means of steel panels and tested under the same earthquake. The seismic performance of the specimen before and after the retrofit was evaluated using FEMA356 standards, and the results were compared in terms of stiffness, strength, and deformability. The results have confirmed effectiveness of the proposed retrofit scheme.
Keywords: Seismic; RC buildings; steel panel; shake table